The Roles of Glutathione, Glutathione Peroxidase, Glutathione Reductase and the Carbonyl Protein in Pulmonary and Extra Pulmonary Tuberculosis - Dalvi, Shubhangi M; Patil, Vinayak W; Ramraje, Nagsen N (Journal of clinical and diagnostic research, 2012)
This study determines the protein carbonyls which cause cellular damage and glutathione, glutathione peroxidase, glutathione reductase act as antioxidants. This study was carried out in different categories of pulmonary and extra pulmonary tuberculosis cases of newly sputum culture positive diagnosed pulmonary categorie I (n=100), extra pulmonary patients categorie (n=35) before and after the DOTS treatment of 6 months, categorie II (n=100), categorie III (n=100) and in normal control subjects (n=100). The serum protein carbonyl levels were significantly increased in the pulmonary and extra pulmonary tuberculosis patients. The activities of blood glutathione, glutathione peroxidase, and glutathione reductase were found to be significantly decreased in subjects of all the categories of pulmonary and extra pulmonary tuberculosis. A negative correlation between the carbonyl protein content and glutathione, glutathione peroxidase, and glutathione reductase was seen in pulmonary tuberculosis, p<0.001. Increased antioxidant defense mechanism due to increase oxidative stress in tuberculosis. The changes were reversed after 6 months of antitubercular treatment in patients with a good recovery, but the increase in the oxidative stress was not completely reversed.